Analisis Proksimat Karbon Aktif Bunga Lontar (Borassus flabellifer L) Teraktivasi Asam Fosfat - Novianty, Iin (Jurnal Kimia dan Ilmu Lingkungan: Chemviro, 2025)
This research aims to determine the chemical properties of activated carbon from palm flowers. Making activated carbon using the drum kiln method. Activation is carried out chemically using phosphoric acid (H3PO4). Proximate analysis is carried out to determine the chemical properties of the carbon produced. The results obtained in this study were water, ash, volatile matter and bound carbon content respectively 8.72%, 21.86%, 4.48% and 73.66%.